2007
DOI: 10.1111/j.1365-2958.2007.06033.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of Helicobacter pylori transcriptional terminators suggests this microbe uses both intrinsic and factor‐dependent termination

Abstract: SummaryIn this study, we report experimental analysis of transcriptional terminators in the human pathogen Helicobacter pylori. Previous bioinformatics approaches came to differing conclusions regarding transcriptional termination in this bacterium. We used a reporter construct, the tnpR-encoded resolvase, to assess terminators. In our first experiments, we found that a subset of previously predicted intrinsic terminators for H. pylori are functional. In our second experiments, we used an unbiased screen to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…In each case, the majority of the open reading frame was deleted in frame and replaced with a cat gene (that lacked its transcriptional terminator), as detailed in Table 1, to create null mutants. Previous work from our lab has shown that this cat allele is not polar (8,24,45), and we verified that genes downstream of fliN, fliM, and fliY were unaffected using reverse transcription-PCR (see Fig. S2 in the supplemental material), suggesting that these mutations are nonpolar.…”
Section: Methodsmentioning
confidence: 50%
“…In each case, the majority of the open reading frame was deleted in frame and replaced with a cat gene (that lacked its transcriptional terminator), as detailed in Table 1, to create null mutants. Previous work from our lab has shown that this cat allele is not polar (8,24,45), and we verified that genes downstream of fliN, fliM, and fliY were unaffected using reverse transcription-PCR (see Fig. S2 in the supplemental material), suggesting that these mutations are nonpolar.…”
Section: Methodsmentioning
confidence: 50%
“…In addition, it efficiently delivers the translocated effector protein CagA to cells in culture, facilitating the cell biological analysis of this important virulence factor (2,8,9,12,13). The strain has also been subjected to multiple experimental adaptations to new environments, including growth on canine kidney epithelial cells (2), serial passage through the mouse stomach (3,5), and adaptation to in vitro growth in the presence or absence of a functional natural transformation system (4). Determination of the complete genome sequence of G27 will facilitate research with this strain and provide a foundation for molecular evolution studies of the genetic basis for its adaptation to new environments.…”
mentioning
confidence: 99%
“…H. pylori strain mG27 is a mouse-adapted descendant of clinical isolate G27 (19,23). mG27 was generated by serially passaging the G27 H. pylori strain in mice (19). All H. pylori strains were cultured on Columbia horse blood agar (CHBA) or in brucella broth supplemented with 10% fetal bovine serum (BB10) and were grown at 37°C under microaerobic conditions with a gas mixture containing 5 to 10% O 2 , 10% CO 2 , and 80 to 85% N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…H. pylori strain mG27 is a mouse-adapted descendant of clinical isolate G27 (19,23). mG27 was generated by serially passaging the G27 H. pylori strain in mice (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation